PARP Inhibitors: From the Mechanism of Action to Clinical Practice - Branco, Cátia (2022)
Repairing damage and errors that occur in the DNA molecule is essential to maintain the integrity of the genome and cell viability. Deficits in DNA repair mechanisms lead to an increased risk of genetic instability and contribute to neoplastic transformation. Poly (ADP-ribose) polymerases (PARP) are a group of enzymes that play a key role in signalling and repairing DNA errors. The inhibition of its activity is a therapeutic strategy that takes advantage of the mechanism of synthetic lethality and that can be used in the treatment of tumours with specific defects in DNA repair pathways, namely in tumours with mutations in the tumour suppressor genes BRCA1 and BRCA2. There are several PARP inhibitors (iPARP), already approved by the USA Food and Drug Administration and the European Medicines Agency used in the treatment of breast, ovarian, pancreatic and prostate cancer. However, as with other target therapies, despite being well tolerated and widely used in the clinical practice, iPARP resistance is common and can be developed through various molecular mechanisms. In this article, we intend to make an updated review on iPARP and its main role in tumour cells, highlighting the several resistance mechanisms that have been recently revealed, as well as the current clinical applications and toxicity associated with this target therapy.